APPROACHES TO INCLUSION OF MODERN AND INNOVATIVE TECHNOLOGIES IN THE PROGRAM OF BOTANY SCIENCE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This paper involves the increase in students’learning motivation because of using technology-based media in a botany class. The differences between the academic results of the students who used computer technology in botany and the students who studied according to the traditional teaching method are analyzed.